September earthquakes impact on the mental health of the affected population and recommended actions - Dení Álvarez-Icaza; María Elena Medina-Mora (Instituto Nacional de Salud Pública, 2018)
Natural disasters are a risk factor for the development of mental disorders, the mental health care of the affected population is a priority. The purpose of this text is to present the diagnosis on the provision of services and mental health needs of those affected by the earthquakes of September, 2017. From these observations it is concluded that a National Program for Mental and Psychosocial Health in Critical Situations and Disasters is essential, whose basic action lines are described in this article.